Search for lepton-flavour-violating decays of Higgs-like bosons - Aaij, R; Beteta, CA; Adeva, B; Adinolfi, M; Aidala, CA; Ajaltouni, Z; Akar, S; Albicocco, P; Albrecht, J; Alessio, F; Alexander, M; Albero, A; et al. (SpringerOpen, 2018)
A search is presented for a Higgs-like boson with mass in the range 45 to 195 GeV/c2 decaying into a muon and a tau lepton. The dataset consists of proton-proton interactions at a centre-of-mass energy of 8 TeV , collected by the LHCb experiment, corresponding to an integrated luminosity of 2 fb −1 . The tau leptons are reconstructed in both leptonic and hadronic decay channels. An upper limit on the production cross-section multiplied by the branching fraction at 95% confidence level is set and ranges from 22 pb for a boson mass of 45 GeV/c2 to 4 pb for a mass of 195 GeV/c2 .